Mobility Patterns of Livestock Keepers in Semi-Arid Communal Rangelands of Namaqualand, South Africa. (1st December 2008) - Samuels, M. Igshaan; Allsopp, Nicky; Hoffman, Timm
Abstract : In arid and semi-arid environments, pastoralists use herd mobility to manage resource variability. We investigated temporal mobility patterns of livestock keepers on the spatially confined commons of Namaqualand, South Africa, between 1997 and 2006. We conducted semi-structured interviews with about 300 livestock keepers from ten villages in the Leliefontein communal area. Herd mobility varies significantly amongst the herds in the different villages. Mobility in Leliefontein is complex and is influenced by environmental, agricultural, social and personal factors. We conclude that even with a high degree of variability in herd movements, the mobility patterns of livestock keepers over the last ten years have remained relatively stable.